Voiding dysfunction in older men. Issue 2 (March 2016) - Chung, Amanda; Noguchi, Naomi; Chan, Lewis; Tse, Vincent
Abstract : Purpose of review: Voiding dysfunction in older men is an important health issue, with significant morbidity and biosocioeconomic burden. Treatment decisions are increasingly complex as many older men also suffer concurrent comorbidities and polypharmacy. A relatively sparse number of publications specifically examine this relevant topic. Recent findings: Common geriatric voiding syndromes include overactive bladder (OAB) and underactive bladder, with nocturia and incontinence often the most bothersome lower urinary tract symptoms, and may represent a falls risk together with OAB and incontinence. The combination of detrusor overactivity and impaired contractility may coexist in older patients and can be particularly difficult to diagnose and treat clinically. A small but not insignificant proportion of older men experience spontaneous remission of OAB symptoms without treatment, and 'watchful waiting' may be a reasonable option. OAB treatment with mirabegron may have a preferable side-effect profile compared with anticholinergics in older men. Intravesical onabotulinum toxin A is effective but risk of retention is greater in the older adults. Benign prostatic obstruction (BPO) and underactive bladder may lead to urinary retention, necessitating surgery or catheterization. BPO surgery is a reasonable option in older men, with realistic counselling of postoperative expectations. Combination BPO surgery and medical OAB treatment is suitable for detrusor overactivity and impaired contractility. Stress incontinence in older patients is usually iatrogenic and treatment can include continence applicances, urethral bulking agents, suburethral sling or artificial urinary sphincter. Summary: Management of voiding dysfunction in older patients need to take into account multiple factors including symptomatic and functional impairment, cognition, comorbidities and polypharmacy. Future research examining pathophysiology and treatment outcomes of voiding dysfunction in the older patient population is increasingly relevant.